Operation of graphene quantum Hall resistance standard in a cryogen-free table-top system. (19th August 2015) - Janssen, T J B M; Rozhko, S; Antonov, I; Tzalenchuk, A; Williams, J M; Melhem, Z; He, H; Lara-Avila, S; Kubatkin, S; Yakimova, R
Abstract: We demonstrate quantum Hall resistance measurements with metrological accuracy in a small cryogen-free system operating at a temperature of around 3.8 K and magnetic fields below 5 T. Operating this system requires little experimental knowledge or laboratory infrastructure, thereby greatly advancing the proliferation of primary quantum standards for precision electrical metrology. This significant advance in technology has come about as a result of the unique properties of epitaxial graphene on SiC.